Utusan damai di kemelut perang : peran zending dalam Perang Toba : berdasarkan laporan L.I. Nommensen dan penginjil RMG lain - Kozok, Uli. (Jakarta : Yayasan Pustaka Obor Indonesia, 2010)
History of Christian missions in Sumatera Utara and role and position of Germany missionaries of Rhenish Mission Society in the Toba War, 1878.
Includes bibliographical references (p. [159]-[163]) and index.
Keywords: Nommensen, L. I. -- 1834-1918.; Rheinische Missionsgesellschaft; Missions -- Indonesia -- Sumatera Utara -- History; Sumatera Utara (Indonesia) -- Church history; Indonesia -- History -- Toba War, 1878.